2013
DOI: 10.15282/jmes.4.2013.6.0039
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Forced Convection Heat Transfer over Staggered Circular Tube Banks: A CFD Approach

Abstract: This paper presents the numerical study of two-dimensional forced convection heat transfer for staggered tube banks in cross flow under incompressible, steady-state conditions. This system is solved for body-fitted coordinates using the finite volume method for flow over a bundle of cylindrical tubes. A constant heat flux is imposed on the surface of the tubes as the thermal boundary condition. The type of arrangement considered is a set of staggered tubes. Ratios of longitudinal pitch to tube diameter (S T /D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…The flow dynamics, heat dissipation and pollutant dispersion in urban areas can be obtained experimentally by on-site/wind-tunnel measurements or numerically by employing computational fluid dynamics (CFD) methods. As computer capabilities improve, CFD becomes more popular with its cost effectiveness and ability to test a wide variety of conditions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The flow dynamics, heat dissipation and pollutant dispersion in urban areas can be obtained experimentally by on-site/wind-tunnel measurements or numerically by employing computational fluid dynamics (CFD) methods. As computer capabilities improve, CFD becomes more popular with its cost effectiveness and ability to test a wide variety of conditions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Only one percent of drinking water sources is available and the rest of them are frozen in polar glaciers (2%) [1]. Some industrial processes such as the ozonation of wastewater [2] , wastewater purification by graphene oxide [3], wastewater purification by biological oscillatory flow reactor [4], wastewater filtration by nano tube bundles filters [5,6], etc. are the main candidates for freshwater production from wastewater sources.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned literature review showed that the effects of various design and operating parameters (i.e. air gap [13], mass flow rate [7,17], wick material [15], internal reflector [19], baffle [17,20], inclined tray [21], steps geometry optimisation [22] and nanofluid [5,6]) on the freshwater productivity of stepped cascade solar still have been investigated. However, the effect of PV/T collector connection to stepped cascade solar still to enhance freshwater productivity is not investigated.…”
mentioning
confidence: 99%
“…Flat tubes seem to have more appropriate pressure drop characteristics than circular tubes [7]. The forced convection heat transfer over a bundle of circular cylinders was investigated numerically [8][9][10][11] and non-square tubes in both in-line and staggered tube arrangements [12][13][14][15][16]. The flow over a bank of elliptical cylinder tubes was presented by Yianneskis et al [17], both numerically and experimentally.…”
Section: Introductionmentioning
confidence: 99%